Positron emission tomography/computerized tomography for tumor response assessment—a review of clinical practices and radiomics studies - Lu, Wei; Chen, Wengen (Translational Cancer Research, 2016)
Even with recent advances in cancer diagnosis and therapy, treatment outcomes for many cancers remain dismal. Patients often show different response to the same therapy regimen, supporting the development of personalized medicine. 18F-fluodeoxyglucose positron emission tomography/computerized tomography (18F-FDG PET/CT) has been used routinely in the assessment of tumor response, in prediction of outcomes, and in guiding personalized treatment. These assessments are mainly based on physician’s subjective or semi-quantitative evaluation. Recent development in radiomics provides a promising objective way for tumor response assessment, which uses computerized tools to extract a large number of image features that capture additional information not currently used in clinic that has prognostic value. In this review, we summarized the clinical use of PET/CT and the PET/CT radiomics studies for tumor response assessment. Finally, we discussed some challenges and future perspectives.